Demographics and significance of porotic hyperostosis as assessed by surface microscopy - Rothschild, Bruce M.; Jellema, Lyman; Lambert, Wayne (Anatomical record (Hoboken, N.J. : 2007), 2022)
Background Examination of parietal surface anatomy has been limited because standard techniques have insufficient resolution to identify and characterize the structures of interest. Perspectives derived thereof have not clarified their nature. Surface microscopy is pursued as a nondestructive technique to assess the character and implications of porotic pores (referred to as porotic hyperostosis), which have been subject of much speculation. Methods The external surface of the skulls, selected on the basis of age and gender, from the Hamann‐Todd human collection are examined by epi‐illumination microscopy for surface pores and to assess correlation with age, ethnicity, gender, anemia, infection, cancer, hypertrophic bone disorders, renal disease, and fractures. Results Pore‐like surface defects are present in 2.7%–5% of individuals in the third‐fifth decades of life; 7%, in the sixth‐eighth; and 25%, in the ninth‐11th, but absent in the second decade of life. They are gender and birthdate independent, but slightly more common in African Americans. Fractures are more common among individuals with parietal pores, while tuberculosis, cancer, and hypertrophic bone diseases and anemia are less common. Discussion This is the first study to actually examine the prevalence of parietal pores as a function of known age, race, and sex and provides a baseline for comparison with populations in which those variables are not clearly identifiable. While some porotic pores may be related to marrow hyperplasia, transcortical circulation may explain the majority.